Recognizing the Role of Historical Houses of Isfahan in Improving the Social Interactions of Residents, Relying on the Lived Experience of People - Pezhman Nazeri Naeini; Maryam Ghasemi Sichani; Mohsen Afshari; Narges Keshti Ara (توسعه پایدار شهری)
Social convergence and creating suitable conditions for its creation is one of the necessities of today's residential architecture. Because it seems that most of the residential buildings of contemporary architecture are not able to create privileged positions to establish suitable social interactions for their residents, and as a result, the result of such an event is the isolation and distance of residents from each other and neglecting the benefits of social architecture. Is. In other words, even though one of the main tasks of houses is to help promote social interactions between the residents of the house, this task has its special feeling in the houses and biological complexes of today's cities (influenced by the rules of contemporary urban planning). have lost Therefore, according to the existing findings, historical houses seem to provide these conditions in a suitable way, the question of the present research is that the reasons for the success of historical houses in this field What is? And what are the effective factors on promoting social interactions in historical houses? Therefore, this research seeks to investigate a number of historical houses in Isfahan city, using the classic foundation data research method and using the opinions of people who have a history of living in these houses, the factors affecting the ability to identify the social interactions in these houses. The results of the research show that, from the point of view of the interviewees, several factors are effective in promoting social interactions in historical houses, all of which have one point in common, and that is "creating physical and mental comfort and peace" for the residents. In addition, in a general classification, these factors can be divided into four categories: physical, functional, cultural-social, sensory-perceptual. Although all these factors have not been emphasized to the same extent from the point of view of the interviewees.